2019
DOI: 10.1073/pnas.1911123117
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism and regulation of the CbbQO-type Rubisco activase, a MoxR AAA+ ATPase

Abstract: The vast majority of biological carbon dioxide fixation relies on the function of ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco). In most cases the enzyme exhibits a tendency to become inhibited by its substrate RuBP and other sugar phosphates. The inhibition is counteracted by diverse molecular chaperones known as Rubisco activases (Rcas). In some chemoautotrophic bacteria, the CbbQO-type Rca Q2O2 repairs inhibited active sites of hexameric form II Rubisco. The 2.2-Å crystal structure of the MoxR A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 53 publications
6
46
0
Order By: Relevance
“…The close proximity of genes encoding an AAA ATPase and a vWA-MIDAS domain protein has been reported in thermophilic archaeal viruses, such as Acidianus Two-Tailed Virus (ATV) [ 54 ]. The interaction between AAA ATPase and a vWA-MIDAS domain protein has been closely studied in several cases, and a common finding is that the vWA-MIDAS domain protein provides an adaptor function, while the AAA ATPase acts as a chaperone [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The close proximity of genes encoding an AAA ATPase and a vWA-MIDAS domain protein has been reported in thermophilic archaeal viruses, such as Acidianus Two-Tailed Virus (ATV) [ 54 ]. The interaction between AAA ATPase and a vWA-MIDAS domain protein has been closely studied in several cases, and a common finding is that the vWA-MIDAS domain protein provides an adaptor function, while the AAA ATPase acts as a chaperone [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This MIDAS-mediated mechanism may be a more general alternative strategy utilized by a subclass of AAA proteins. One example is the MoxR-group AAA protein CbbQ, a Rubisco activase that requires a MIDAS-containing cofactor protein to function (32)(33)(34). Recent structural work has shown that the MIDAScontaining von Willebrand factor A (VWA) domain of this cofactor docks onto the hexameric AAA ring of CbbQ in a bimolecular interaction, and furthermore that the VWA domain communicates information about substrate binding to the AAA ring (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast the CbbQO-type Rca found in chemoautotrophic proteobacteria consists of a cup-shaped AAA+ hexamer (CbbQ 6) bound to a single adaptor protein CbbO, which is essential for Rubisco activation (9). During Rca function the hexamer remodels CbbO, which is bound to inhibited Rubisco via a von Willebrand Factor A domain (16).…”
Section: Introductionmentioning
confidence: 99%